The Wider Spatial-Economic Impacts of High-Speed Trains: A Comparative Case Study of the Lille and Manchester Sub-Regions - Chia-Lin Chen; Peter Hall (European Regional Science Association (ERSA), 2010)
This paper will present empirical evidence on the wider spatial-economic impacts of High Speed Trains (HSTs) at the intra-regional level. It represents follow-up research to a previous empirical study at inter-regional level, based on UKIC125- an upgraded HST system. The findings suggest that HST has had substantial and demonstrable effects in aiding this transition within a 2-hour travel limit of London, but that the effects have not been automatic or universal. The need for integrated planning combining transport, economic, and spatial issues to promote dynamic city-region development should not be overlooked. Particularly, the UK is currently situated at the critical turning point considering a long-term commitment to High Speed Two (HS2): whether, to what extent, and how the arrival of a HST hub in a city could act as the agent of change for transforming surrounding sub-regions. Thus, a finer-grained and deeper-probing analysis at the intra-regional scale is needed, in the form of comparative case studies of two post-industrial city-regions. Lille/Pas-de-Calais and the Manchester city-region are chosen, the first to examine the effects of the TGV after its arrival in 1994, the second to provide a prognosis for Manchester and its neighbouring towns after the projected arrival of HS2. In the Lille Métropole, the TGV brought about a dramatic change in economic fortunes. But, within the wider Nord-Pas de Calais region, two divergent developmental trajectories of traditional manufacturing industries have increasingly manifested themselves: Lille Métropole has increasingly strengthened its service-based growth, whereas the former coal area and coastal region seems not to have attracted knowledge-based development. In the Manchester city-region, the new generation of 300 k/hr HST lines will undoubtedly in their turn have major spatial-economic impacts as Manchester is brought closer to London with the dramatic shrinking of critical time-distance. The relationship between Manchester and its neighbouring towns may however be negative to poorly connected towns like Burnley which is reflected in its weak economic performance. Overall, this research aims to fill in the gap with empirical evidence of intra-regional impacts of HSTs and disentangle the complex forces and the developmental phases in the dynamic process of city-region regeneration.
Keywords: 330